2009
DOI: 10.1105/tpc.109.067678
|View full text |Cite
|
Sign up to set email alerts
|

MAP KINASE PHOSPHATASE1 and PROTEIN TYROSINE PHOSPHATASE1 Are Repressors of Salicylic Acid Synthesis and SNC1-Mediated Responses inArabidopsis   

Abstract: Mitogen-activated protein (MAP) kinase phosphatases are important negative regulators of the levels and kinetics of MAP kinase activation that modulate cellular responses. The dual-specificity phosphatase MAP KINASE PHOSPHATASE1 (MKP1) was previously shown to regulate MAP KINASE6 (MPK6) activation levels and abiotic stress responses in Arabidopsis thaliana. Here, we report that the mkp1 null mutation in the Columbia (Col) accession results in growth defects and constitutive biotic defense responses, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
288
2
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(319 citation statements)
references
References 77 publications
(110 reference statements)
17
288
2
12
Order By: Relevance
“…The MAP kinase kinase4 (MKK4) is known to activate MPK3 and MPK6 (Asai et al, 2002;Kim et al, 2011). Next, we transformed cells with constitutive active MKK4 EE to activate downstream MAP kinases MPK3 and MPK6 (Bartels et al, 2009) together with either the wild type or Ser309Ala mutant of HSFA4A, which led to a steady increase of pHSP17.6A-LUC transactivation reaching about 18-fold increase upon 40 h with the wild type but was around 50% less with the Ser-309Ala mutant form of HSFA4A (Fig. 9C).…”
Section: Phosphorylation Of Hsfa4a Enhances Transient Transactivationmentioning
confidence: 99%
“…The MAP kinase kinase4 (MKK4) is known to activate MPK3 and MPK6 (Asai et al, 2002;Kim et al, 2011). Next, we transformed cells with constitutive active MKK4 EE to activate downstream MAP kinases MPK3 and MPK6 (Bartels et al, 2009) together with either the wild type or Ser309Ala mutant of HSFA4A, which led to a steady increase of pHSP17.6A-LUC transactivation reaching about 18-fold increase upon 40 h with the wild type but was around 50% less with the Ser-309Ala mutant form of HSFA4A (Fig. 9C).…”
Section: Phosphorylation Of Hsfa4a Enhances Transient Transactivationmentioning
confidence: 99%
“…Moreover, Ca 2+ /CaM binds to plant catalase and enhances its activity (Yang and Poovaiah, 2002b). Recently, Ca 2+ /CaM was also reported to regulate H 2 O 2 -mediated defense responses by regulating the MAPK cascade through the action of MAPKs and MAPK phosphatases (Lee et al, 2008;Bartels et al, 2009;Takahashi et al, 2011).…”
Section: The Best Characterized Cam-regulated Transcription Factorsmentioning
confidence: 99%
“…Consistent with enhanced PAMP responses, the mkp1 mutant also displayed enhanced resistance to the virulent pathogen Pseudomonas syringae pv tomato DC3000 (hereafter referred to as DC3000). The enhanced PAMP-induced growth inhibition and resistance in mkp1 are specifically dependent on MPK6, indicating a genetic interaction between MKP1 and MPK6 (Bartels et al, 2009;Anderson et al, 2011). Because of the importance of these negative regulators in modulating defense responses, it is also critical to understand how phosphatases such as MKP1 are regulated.…”
mentioning
confidence: 99%
“…However, the regulation of MKPs during PAMP responses in plants is not well understood. Both in vitro and in vivo studies have shown that Arabidopsis MKP1 interacts with three MAPKs (MPK3, MPK4, and MPK6), with the strongest interaction being with MPK6 (Ulm et al, 2002;Bartels et al, 2009). In addition, Arabidopsis MKP1 was shown to be phosphorylated in vitro by MPK6, and phosphorylation increased the phosphatase activity of MKP1, indicating that phosphorylation may be an important regulatory mechanism of MKP1 (Park et al, 2011).…”
mentioning
confidence: 99%